2016
DOI: 10.1186/s12889-016-3658-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human immunodeficiency virus and hepatitis B virus infections in young women seeking abortion care in Ethiopia: a cross - sectional study

Abstract: BackgroundYoung women aged 15–24 years are members of key populations at higher risk for Human Immunodeficiency Virus (HIV) acquisition through sexual intercourse. In areas where unprotected sex is a common practice, Hepatitis B virus (HBV) commonly transmitted via sexual and parenteral routes. The study aimed at determining HIV and HBV infections prevalence in young women attending health institutions for abortion care in Bahir Dar city, Ethiopia.MethodsA cross - sectional study was conducted from January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
3
9
3
Order By: Relevance
“…This could be one prominent reason history of abortion and being in the age under 20 has a similar effect on pregnant mothers’ sero-positivity for HBsAg. This was similar to the finding reported by, 35 where the proportion of HBV infection was significantly higher in the age group between 15 and 17 years old 30 and, <25-yearold pregnant women.…”
Section: Discussionsupporting
confidence: 92%
“…This could be one prominent reason history of abortion and being in the age under 20 has a similar effect on pregnant mothers’ sero-positivity for HBsAg. This was similar to the finding reported by, 35 where the proportion of HBV infection was significantly higher in the age group between 15 and 17 years old 30 and, <25-yearold pregnant women.…”
Section: Discussionsupporting
confidence: 92%
“…However, the prevalence rate in this study is lower than the 9.7% in Buea health district [11] and 7.7% in the North West region of Cameroon [21]. The prevalence rate in this study is higher than the 1.94% seroprevalence of HBsAg among pregnant women attending ANC clinic in Ethopia [22]. The observed difference in HBV distribution across the different geographical location might be attributed to variation in socio demographic characteristics of the study population such as socio-cultural environment, cultural practices, sexual practices, medical exposure and the difference in hepatitis epidemiology.…”
Section: Discussionmentioning
confidence: 68%
“…It is the leading cause of liver disease and the risk of developing hepatocellular carcinoma increased in patients with chronic HBV infection. 4 In sub-Saharan Africa, 26% of liver cancer is due to HBVand 19 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) per 1000 deaths attributed due to it. 5 The prevalence of chronic hepatitis B virus infection in sub-Saharan Africa ranges from 5% to 25%.…”
Section: Introductionmentioning
confidence: 99%
“…Most reports regarding HBV were from institutional-based studies and among the high-risk group of people. [18][19][20][21][22] Even though few community-based studies on seroepidemiology of HBV prevalence in Ethiopia have been previously done and indicated that hepatitis B is endemic in Ethiopia with regional variation, 15,23 community-based studies are still limited. This study aimed to determine the seroprevalence of HBsAg among adults within the community and identify factors associated with hepatitis B virus infection in Southwest Ethiopia.…”
Section: Introductionmentioning
confidence: 99%